Seksualność kobieca w Pięćdziesięciu twarzach Greya. Powieściowa fikcja soft-porno czy kulturowe przesunięcie? - Gromkowska-Melosik, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2014)
The purpose of my text is an attempt to define the context of the global fascination of super-bestseller, the book Fifty Shades of Grey – regardless of the fact that literary critics agreed that this is a novel very poor in every aspect. What makes this erotic-romantic story so exceptional, among others, to the extent that it meets with a huge “cultural vindictiveness”, entering into public discourse invasively, while hundreds of others – good or bad books are ignored? The main context of interest/fascination with the book Fifty Shades of Grey, in my opinion, is associated with putting again – and doing it radically – question about the permitted forms of female sexuality. Here we are dealing with a sudden shift – by the author – the debate in this area “a few miles ahead” and cancellation of several important tenets, including the dogma of women as innocent virgin, the dogma of women as mothers and wives but also feminist dogma of women socially and sexually liberated from the domination of men.